Review of Auditor-General's reports 1997-98 : third quarter - Australia. Parliament. Joint Committee of Public Accounts and Audit (Canberra : [Ausinfo], 1999)
This report is the review by the Joint Committee of Public Accounts and Audit (JCPAA) of the Auditor-General's reports tabled in the third quarter of 1997-98. From these, the Committee selected three reports for further examination. The Committee reviewed Audit Report No. 35, into the then DEETYA International Services, Department of Employment, Education, Training and Youth Affairs, (DIS) because of concerns raised in the report about DIS' operational framework. The audit report found that DIS' mission statement and planning documents pointed to a commercial operation, but the level of "commerciality" it wished to achieve had not been clearly defined. Audit report No. 38 into the sale of Brisbane, Melbourne and Perth Airports reviewed the extent to which the Government's sales objectives were achieved. The issues on which the Committee focussed included the sale management; the bid assessment and the sale outcome. A specific area of concern was the weakness in the contracting process. The selection of Audit Report No. 39 into the Child Support Agency (CSA) for further scrutiny, was made on the basis of continuing negative community perceptions about the administration of the Child Support Scheme.
1. Introduction -- 2. Audit report no. 35, 1997-98, DEETYA International Services, Department of Employment, Education, Training and Youth Affairs -- 3. Audit report no. 38, 1997-98, Sale of Brisbane, Melbourne and Perth airports -- 4. Audit report no. 39, 1997-98, Selected functions of the Child Support Agency.
"March 1999".
Reviews: Audit Report no.35 1997-98 "DEETYA International Services, Department of Employment, Education, Training and Youth Affairs"; Audit Report no.38 1997-98 "Sale of Brisbane, Melbourne and Perth airports"; and Audit Report no.39 1997-98 "Selected functions of the Child Support Agency".
Includes: Transcript of evidence (official Hansard report) from Committee hearing in Canberra on Tuesday, 16 June 1998
Keywords: Australian Taxation Office. -- Child Support Agency; Australia. -- Department of Employment, Education, Training and Youth Affairs; Australian National Audit Office; Privatization -- Australia; Administrative agencies -- Australia -- Auditing; Child support -- Australia; Finance, Public -- Australia -- Auditing; Public finance -- Australia -- Auditing